Enhanced killing of penicillin-treated gram-positive cocci by human granulocytes: role of bacterial autolysins, catalase, and granulocyte oxidative pathways. - Isturiz, R. (Yale Journal of Biology and Medicine, 1985)
Staphylococci pretreated with subminimal inhibitory concentrations (subMIC) of cell-wall active antibiotics exhibit increased susceptibility to killing by human polymorphonuclear leukocytes (PMNs), even when phagosome information is impaired by the mold metabolite, cytochalasin B. To investigate the role of specific bacterial factors in the process, studies were carried out with organisms lacking catalase (streptococci) or cell-wall autolytic enzymes and compared to findings with Staphylococcus aureus 502A. Neutrophil factors were studied using inhibitors, oxygen radical scavengers, myeloperoxidase (MPO)-deficient PMNs, or PMNs from a patient with chronic granulomatous disease (CGD). Documentation of the enhanced susceptibility of the streptococcal strains to killing by PMNs following subMIC penicillin pretreatment required the use of cytochalasin B. Enhancement of killing occurred independent of the presence or absence of bacterial autolysins or catalase. SubMIC penicillin pretreatment of S. pneumoniae R36A specifically promoted the susceptibility of these organisms to killing by myeloperoxidase (MPO)-mediated mechanisms (enhancement lost using MPO-deficient or azide-treated cells). Factors other than MPO or toxic oxygen products generated by the PMN respiratory burst are responsible for enhanced killing of penicillin-pretreated S. aureus 502A (enhancement preserved using MPO-deficient, azide-treated, or chronic granulomatous disease patient cells). These studies define methods to study the interaction of antimicrobial agents and PMNs in the killing of microorganisms. They also demonstrate that penicillin treatment can change the susceptibility of gram-positive cocci to the action of specific PMN microbicidal mechanisms. The mechanism of the enhancement appears to be bacterial strain-dependent and not predictable by bacterial autolysin or catalase activity.